2015
DOI: 10.1080/11250003.2015.1018351
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of brown trout (Salmo truttaLinnaeus, 1758) (Teleostei: Salmonidae) in its southwesternmost European limit: possible causes

Abstract: Andalusian brown trout populations represent the southwestern limit of this species in Europe, show a high genetic diversity, are subjected to extreme habitat conditions and environmental alterations, and are very sensitive to extinction. However, there is a lack of scientific studies on them. A necessary first step to preserve them is to describe their spatial distribution. We detected the species in eastern Andalusia along almost 710 km of rivers, finding 38 populations inhabiting streams and reservoirs in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 59 publications
(61 reference statements)
1
11
0
Order By: Relevance
“…From the distribution limits of brown trout in the southernmost basins of the Iberian Peninsula (Larios‐López, Tierno de Figueroa, Alonso, et al, 2015), the spatial structure of the local populations in the study region was identified through a detailed field study that searched for any physiographic feature that prevents the population connection between watercourses inhabited by the species (Table S2).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the distribution limits of brown trout in the southernmost basins of the Iberian Peninsula (Larios‐López, Tierno de Figueroa, Alonso, et al, 2015), the spatial structure of the local populations in the study region was identified through a detailed field study that searched for any physiographic feature that prevents the population connection between watercourses inhabited by the species (Table S2).…”
Section: Methodsmentioning
confidence: 99%
“…During 2008 and 2009, intense habitat mapping was conducted on foot with the aims of locating (a) the upper and lower limits reached by trout populations in the studied rivers (Larios‐López, Tierno de Figueroa, Alonso, et al, 2015) and (b) impassable obstacles (waterfalls, dams, etc.) present in their channels (Table S2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in distribution, phenology, population structure and dynamics of freshwater fish have been described or predicted in response to climate change (Comte, Buisson, Daufresne, & Grenouillet, 2013;Comte, Murienne, & Grenouillet, 2014;Harrod, Graham, & Mallela, 2009;Kovach et al, 2016;Nakano, Kitano, & Maekawas, 1996;Xenopoulos et al, 2005), and they have the potential to alter fishmussel interactions. For example, increasing temperatures might negatively affect cold-water stream fishes like salmonids that are near the edge of their distribution, which may contribute to their extirpation or shift their distribution to more suitable areas at higher latitudes or altitudes (Larios-López, Tierno De Figueroa, Alonso-Gonzalez, & Nebot Sanz, 2015). According to Almodóvar, Nicola, and Benigno (2012), warming will lead to the widespread decline of brown trout (Salmo trutta, Salmonidae) across Iberian Peninsula, an area that represents the southern limit of the species distribution.…”
Section: Climate Changementioning
confidence: 99%
“…The study took place from the 1st of December 2014 to the 16th of January 2015. Common trout, Salmo trutta , was present in the experimental reach (Larios‐López, Tierno de Figueroa, Alonso‐González, & Nebot Sanz, , Larios‐López personal communication). Due to the small size and relatively shallow depth of the studied reach, large trout are very scarce or absent; therefore, small individuals dominate the trout population (Larios‐López, based on an unpublished study using electrofishing performed between 2006 and 2014).…”
Section: Methodsmentioning
confidence: 99%